Supercapacitor electrode material with trinickel disulfide-loading halloysite nanotubes and preparation method of supercapacitor electrode material - LI YANAN; ZHOU JIE; TANG WEIHUA; LIU YUN; TANG JIAN (2018)
The invention discloses a supercapacitor electrode material with trinickel disulfide-loading halloysite nanotubes and a preparation method of the supercapacitor electrode material. According to the preparation method of the supercapacitor electrode material, sodium hexametaphosphate is used to pre-treat natural halloysite nanotubes, so that halloysite nanotubes which are easy to agglomerate are removed; a silane coupling agent KH-590 is adopted to perform surface treatment on the halloysite nanotubes, so that sulfydryl-modified halloysite nanotubes are obtained; the sulfydryl-modified halloysite nanotubes, glucose and nickel chloride hexahydrate are mixed uniformly in an ethanol solution, thiourea and ammonia are added into an obtained solution so as to react with the solution; trinickel disulfide is loaded on the surfaces of the halloysite nanotubes; and the supercapacitor electrode material with the trinickel disulfide-loading halloysite nanotubes can be obtained. The supercapacitorelectrode material with t